Antifeedant Activity of Barleria Buxifolia (Linn.) (Acanthaceae) Against Spodoptera Litura Fabricius and Helicoverpa Armigera Hübner (Lepidotera:Noctuidae) - Jeyasankar, A; Chinnamani, T; Chennaiyan, V; Ramar, G (International Journal of Natural Sciences Research, 2014)
To investigate the antifeedant activity of crude extracts of Barleria buxifolia tested against fourth instar larvae of Spodoptera litura and Helicoverpa armigera. Antifeedant activity of hexane, chloroform and ethyl acetate extracts were prepared and tested against fourth instar larvae of selected insect pests. Ethyl acetate extracts of B. buxifolia, showed higher percentage of antifeedant, activity. This is first report on selected economically important pests. Further, the active compounds will be isolate from the ethyl acetate extracts which will be useful for controlling economically important insect pests.